Association between creatinine clearance and lumbar bone mineral density in Chinese patients with osteoporotic fractures: a retrospective cross-sectional study - Su, Ming; Zhou, Peng; Feng, Li-long; Shan, Hui-qiang; Xu, Min-zhe; Gong, Ya-qin; Jin, Jian; Hu, Wen-bin; Lu, Ke; Li, Chong; Yin, Yi (Frontiers in Endocrinology, 2026)
BackgroundCreatinine clearance (CCR) is an important marker of renal function. The association between CCR and lumbar bone mineral density (BMD) in patients with osteoporotic fractures (OPFs) remains unclear. With the increasing prevalence of OPFs in aging populations and the complications associated with renal impairment, understanding this relationship is essential for optimizing patient outcomes.MethodsA total of 1,313 patients with OPFs (aged ≥50 years) were retrospectively analyzed. Patient CCR, lumbar BMD, and relevant clinical data were collected. Lumbar BMD (g/cm2) served as the outcome variable, while baseline CCR was the exposure variable. Multivariate analyses were performed with adjustments for multiple covariates.ResultsIn fully adjusted multivariate regression analysis, baseline CCR showed a significant positive correlation with lumbar BMD (β = 0.16; 95% CI: 0.13–0.18; P < 0.01). A threshold effect was identified in the CCR–BMD relationship, characterized by an inflection point at approximately 130 mL/min CCR. Below this threshold, higher CCR was associated with increased lumbar BMD. Above 130 mL/min, further increases in CCR were not associated with further BMD gains (β = –0.05, P = 0.18). Mean lumbar BMD values increased across CCR tertiles (0.69 ± 0.13, 0.73 ± 0.14, and 0.81 ± 0.15 g/cm2; P < 0.01).ConclusionCCR was positively associated with lumbar BMD among elderly patients with OPFs, showing a non-linear relationship characterized by a CCR threshold (~130 mL/min). These findings highlight the potential importance of renal function assessment in osteoporosis risk evaluation and fracture management.